TINGKAT FILOGENETIK RHOPALOCERA DI TAMAN WISATA ALAM KERANDANGAN KABUPATEN LOMBOK BARAT - Nofisulastri, Nofisulastri; Ayuningtiyas, Monika (Bioscientist : Jurnal Ilmiah Biologi, 2019)
This study aimed to determine the existence of the sub-order species Rhopalocera in Kerandangan Nature Tourism Park (NTP) area and the extent of its phylogenetic level between species found. This type of research was quantitative descriptive research. The sampling location consists of two location points namely the location of the park (the front part of NTP) as station I and the waterfall area of the cave wallet used as station II. Sampling was carried out by estimating the distribution of time ie morning and afternoon with observations for 2 (two) weeks. Sample footage used exploratory survey (roaming) with entrapping method. Data were analyzed descriptively to show a description of the morphology of the species found. Then the similarity level index of soransen was calculated with a limit of 9 species based on the number of species found. The results showed that the types of sub-order Rhopalocera found were Troides helena, Papilio memnom, Graphium sarpedon, Papilio peranthus, Doleschallia bisaltide, Cupha erymanthis, Mycalesis sp., and Jamides alecto. While the closest phylogenetic level falls on Papilio polytes and Papilio peranthus is 100% and species with the farthest kinship level are between species of Papilio polytes and Doleschallia bisaltide with a percentage of phylogenetic is 57,9%.